Prevalent Estimates of HIV/AIDS in Chronically Ill patients admitted in JPMC Karachi Pakistan - Muhammad Anwar, Noshaba Rahat, Humera Shahzad, Amtul Qudos, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the prevalence of HIV/AIDS in chronically ill patients admitted in tertiary care hospital JPMC(Jinnah Postgraduate Medical Centre) Karachi. Study design & place: This cross-sectional study was conducted at JPMC during the June, 2021 to April, 2022. Materials & Methods: A total of 500 patient age ≥18 years having highly suspicious history & symptoms of HIV/AIDS, admitted in Medical & pulmonology department were included in this study. A well-structured questionnaire was used to obtain background characteristics, clinical symptoms; history of high risk behaviors and I/V drug use of all participants was collected. Confidentiality was assured of all participants given unique identification number. Data was analyzed by using Statistical Package for Social Sciences version 21 (SPSS 21). Results: A total of 500 patients comprised of 373 (74.6%) male and 127 (25.4%) female, male to female ratio was 2.93:1. The mean age was 33.5 ± 12.78 years (18 to 83 years). We observed that most of patients belong with history of blood transfusion, 160 (32%) followed by I/V drug user 130 (26%) and sexual contact 96 (19.2%) cases. Out of 500 study participants, 29(5.8%) subjects were HIV/AIDS positive. The results of this study will provide information and awareness about the transmission of HIV in community. The study revealed that the blood transfusion is a significant risk factor in transmission of HIV. The findings of current study will help doctors for postoperative pain treatment following major abdominal surgery. Acute pain management in hospitals faces some significant obstacles, according to a recent review on postoperative pain management procedures in tertiary care facilities center. Conclusion: Most of the chronically ill patients admitted were men who had been diagnosed with HIV/AIDS. Blood transfusion history, intravenous drug use, and multiple sex partners were important risk factors. There is a need to create awareness among the general public about the risk factors for HIV/AIDS to decelerate the spread of this deadly disease. Keywords: AIDS Acquired immunodeficiency syndrome Chronic diseases, HIV Human Immunodeficiency Virus, Injecting drug user, Multiple sex partners, JPMC Jinnah Postgraduate Medical Centre